DAMPAK PERNIKAHAN DINI TERHADAP ANGKA PERCERAIAN DI KECAMATAN KALIBARU KABUPATEN BANYUWANGI - Edy Imam Supeno (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Marriage at a young age often has a negative impact both personally and socially, so if not anticipated, early marriage will not result in family happiness. One of the main factors that cause early marriage is the low level of education, which affects the mindset and understanding of the nature and purpose of marriage. This study uses a qualitative descriptive method with an explanatory descriptive qualitative approach. Primary data was collected through observation, interviews, and documentation, while secondary data was obtained from the literature. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that young divorce victims, especially women, experience a change in social status to become young widows, so they must be economically independent. Personal impacts that arise include trauma and depression, while social impacts are in the form of difficulty adapting to the environment. Factors that cause divorce at a young age include economic problems, infidelity, lack of harmony in the household, the inability of the husband to provide for the family, and lack of openness between spouses.